Bioturbation of Ag2S-NPs in soil columns by earthworms. (September 2019) - Baccaro, Marta; Harrison, Samuel; van den Berg, Hans; Sloot, Laura; Hermans, Davy; Cornelis, Geert; van Gestel, Cornelis A.M.; van den Brink, Nico W.
Abstract: Sewage sludge contains Ag2 S-NPs causing NP exposure of soil fauna when sludge is applied as soil amendment. Earthworm bioturbation is an important process affecting many soil functions. Bioturbation may be affected by the presence of Ag2 S-NPs, but the earthworm activity itself may also influence the displacement of these NPs that otherwise show little transport in the soil. The aim of this study was to determine effects of Ag2 S-NPs on earthworm bioturbation and effect of this bioturbation on the vertical distribution of Ag2 S-NPs. Columns (12 cm) of a sandy loamy soil with and without Lumbricus rubellus were prepared with and without 10 mg Ag kg −1, applied as Ag2 S-NPs in the top 2 cm of the soil, while artificial rainwater was applied at ∼1.2 mm day −1 . The soil columns were sampled at three depths weekly for 28 days and leachate collected from the bottom. Total Ag measurements showed more displacement of Ag to deeper soil layers in the columns with earthworms. The application of rain only did not significantly affect Ag transport in the soil. No Ag was detected in column leachates. X-ray tomography showed that changes in macro porosity and pore size distribution as a result of bioturbation were not different between columns with and without Ag2 S-NPs. Earthworm activity was therefore not affected by Ag2 S-NPs at the used exposure concentration. Ag concentrations along the columns and the earthworm density allowed the calculation of the bioturbation rate. The effect on the Ag transport in the soil shows that earthworm burrowing activity is a relevant process that must be taken into account when studying the fate of nanoparticles in soils. Graphical abstract: Image 1 Highlights: Earthworms bioturbation lead to transport of Ag2 S-NPs in the soil columns. Rainfall does not affect the transport of Ag along the soil column in unsaturated soil conditions. Bioturbation is not affected by the presence of Ag2 S-NP in the top soil and earthworms do not avoid Ag2 S-NPs. Bioturbation of the soil needs to be taken into account when studying the fate and transport of NPs. Abstract : Earthworm bioturbation plays a more important role than rainfall in the vertical transport of Ag2 S-NPs in soil.